Matrix Gla Protein Binds to Fibronectin and Enhances Cell Attachment and Spreading on Fibronectin - Satoru Ken Nishimoto; Miyako Nishimoto (International Journal of Cell Biology)
Background. Matrix Gla protein (MGP) is a vitamin K-dependent, extracellular matrix protein. MGP is a calcification inhibitor of arteries and cartilage. However MGP is synthesized in many tissues and is especially enriched in embryonic tissues and in cancer cells. The presence of MGP in those instances does not correlate well with the calcification inhibitory role. This study explores a potential mechanism for MGP to bind to matrix proteins and alter cell matrix interactions. Methods. To determine whether MGP influences cell behavior through interaction with fibronectin, we studied MGP binding to fibronectin, the effect of MGP on fibronectin mediated cell attachment and spreading and immunolocalized MGP and fibronectin. Results. First, MGP binds to fibronectin. The binding site for MGP is in a specific fibronectin fragment, called III1-C or anastellin. The binding site for fibronectin is in a MGP C-terminal peptide comprising amino acids 61–77. Second, MGP enhances cell attachment and cell spreading on fibronectin. MGP alone does not promote cell adhesion. Third, MGP is present in fibronectin-rich regions of tissue sections. Conclusions. MGP binds to fibronectin. The presence of MGP increased cell-fibronectin interactions.